2021
DOI: 10.22271/tpi.2021.v10.i5l.6325
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review on sea buckthorn: Biological activity and its potential uses

Abstract: This review is result of various research and studies of comprehensive material regarding nutritional composition, biological activities as well as uses of sea buckthorn as food, medicine, cosmeceuticals, and feed. Sea buckthorn holds unique nutritional composition with Vitamins (A, C, D, E, F, K, P, and B complex vitamins), 18 free amino acid and unique unsaturated fatty acid profile that makes berry only plant source of omega-7 fatty acid. Its bioactive phytochemical compounds possess various biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…WC, TSS, SSC and TA were important attributes which affected the quality of sea buckthorn berries [ 22 ]. With the extension of freezing time, the WC, TSS, SSC and TA contents of the berries steadily decreased, and frozen at −30 °C for 45 d were lower than those frozen at 0 d by 13.0%, 10.9%, 29.2% and 21.0%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…WC, TSS, SSC and TA were important attributes which affected the quality of sea buckthorn berries [ 22 ]. With the extension of freezing time, the WC, TSS, SSC and TA contents of the berries steadily decreased, and frozen at −30 °C for 45 d were lower than those frozen at 0 d by 13.0%, 10.9%, 29.2% and 21.0%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The works [1][2][3] provide a large number of research results devoted to the study of the beneficial properties of sea buckthorn and its processing products. It has been shown that sea buckthorn (Hippophae rhamnoides L.) is a valuable multipurpose plant that is widely grown in Asia, Europe and Canada.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…But in [1], the increase of biologically active substances in raw materials remains an unresolved problem. Thus, it was noted [3] that sea buckthorn has a unique nutritional composition with vitamins (A, C, D, E, F, K, P and B), 18 free amino acids and a unique profile of unsaturated fatty acids, which makes this berry a plant source of omega-7 fatty acids. The components of sea buckthorn have various biological properties: antioxidant, immunomodulatory, anticarcinogenic, hepatoprotective, cardioprotective, antiatherogenic and radioprotective.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Sea buckthorn (SB) was used traditionally for its medical and nutritional qualities (Vilas-Franquesa et al, 2020). SB as well as the sea buckthorn meal (SBM) are rich in nutraceuticals as: vitamins A, B1, B2, B6, C, fatty acids, minerals and polyphenols with important anti-inflammatory and antioxidant properties (Shah et al, 2021). SB oil has a unique composition of fatty acids, the seeds being rich in polyunsaturated fatty acids (-3 and -6) fatty acids, while in the pulp there are mainly omega-7 fatty acids (Teleszko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%